From genetic association to molecular mechanism. - van de Bunt, M; Gloyn, A (2010)
Over the past 3 years, there has been a dramatic increase in the number of confirmed type 2 diabetes (T2D) susceptibility loci, most arising through the implementation of genome-wide association studies (GWAS). However, progress toward the understanding of disease mechanisms has been slowed by modest effect sizes and the fact that most GWAS signals map away from coding sequence: the presumption is that their effects are mediated through regulation of nearby transcripts, but the identities of the genes concerned are often far from clear. In this review we describe the progress that has been made to date in translating association signals into molecular mechanisms with a focus on the most tractable signals (eg, KCNJ11/ABCC8, SLC30A8, GCKR) and those in which human, animal, and cellular models (FTO, TCF7L2, G6PC2) have provided insights into the role in T2D pathogenesis. Finally, the challenges for the field with the advent of genome-scale next-generation resequencing efforts are discussed.